Community-based infant and young child feeding in emergencies: Lessons from the 2022 Cianjur earthquake for disaster preparedness and resilience - Firda Dewi Yani; Fatmah Fatmah; Fajar Tri Waluyanti (Calamity: A Journal of Disaster Technology and Engineering, 2026)
Background: Infant and young child feeding (IYCF) remains a critical yet often overlooked component of disaster preparedness and response, particularly for infants and young children who are highly vulnerable to nutritional disruption during emergencies. This study aims to analyze community perceptions and complementary feeding practices for children aged 6–23 months during the 2022 Cianjur earthquake in Indonesia, and to explore their implications for community-based disaster preparedness and resilience.  Methods: A qualitative case study design was used in Cijedil Village, one of the areas severely affected by the earthquake. The study involved 18 participants, consisting of nine mothers or caregivers of children aged 6–23 months and nine Posyandu cadres, selected through purposive sampling. Data were collected through focus group discussions and analyzed using thematic analysis. Findings: Caregivers’ understanding of IYCF was limited and uneven. Although some caregivers were familiar with complementary feeding, many had incomplete knowledge of age-appropriate texture, feeding frequency, dietary diversity, food safety, and continued breastfeeding. During the early emergency phase, complementary feeding practices were shaped by survival needs and constrained by limited food access, damaged household facilities, and reliance on general food aid, adult meals, instant foods, and formula milk. The establishment of an IYCF kitchen improved access to more appropriate and diverse food for young children, but its delayed implementation revealed a preparedness gap in child-specific feeding support. Conclusion: Posyandu cadres as grassroots actors played  important roles through household outreach, caregiver communication, child identification, and food distribution. However, their role remained dependent on external support. This study recommends that future disaster preparedness should strengthen caregiver education, cadre capacity, child-specific data systems, information management for emergency nutrition services, integration of IYCF considerations into public kitchen and food assistance mechanisms. Novelty/Originality of this article: This study emphasizes IYCF in emergencies as both a response priority and a preparedness agenda, highlighting the importance of community empowerment in building nutrition-sensitive and resilient disaster management systems.